HUBUNGAN ASUPAN SERAT, LEMAK, DAN POSISI BUANG AIR BESAR DENGAN KEJADIAN KONSTIPASI PADA LANSI - Vita Rizky Pradani Sugiyanto; M. Zen Rahfiludin; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Constipation is considered it is normal, but if not addressed can lead to more serious situations such as impaction (stool become hard and dry) and obstruction. An increase in these complaints with increasing age, around 30–40% of people over 65 years old complaining of constipation. The purpose of this research is to analyze the relationship of the intake fiber, fat, and position of defecation with constipation in the elderly in Social Rehabilitation Unit “Pucang Gading” Semarang. This research use a kind of explanatory research with cross sectional approach. The population of the research was the whole of the elderly living in Social Rehabilitation “Pucang Gading” Semarang with a total 77 people. The subject of research as many as 35 people selected by purposive. Data analysis using Chi Square and Rank Spearman. The results showed as much as 40% elderly experiencing constipation, fiber intake enough category of elderly 54,3%, fat intake enough category of elderly 74,3%, and the position of the defecation squat of 68,6%. There is a relationship between fiber intake with constipation (p = 0,013) and there is a relationship between fiber intake with a period of defecation (p=0,026). There is no relationship between fat intake with constipation (p = 0,432) and there is a relationship between fat intake with a period defecation (p=0,010). There is a relationship between the position of defecation with constipation (p = 0,011). The study recomemends to the chef or manager Social Rehabilitation “Pucang Gading” Semarang serves food with the texture that is soft that the elderly can chew the food especially food containing sources of fiber such as vegetables and fruits.